Implementasi Model Pembelajaran Flipped Classroom dalam Mengembangkan Life Skill Pada Pembelajaran PAI di SMK Al-Mahrusiyah Ngampel Kota Kediri - Nurhidayat, Amin (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2023)
The aims of this study were (1) Flipped classroom design to develop life skills (life skills) in PAI learning, (2) Implementation of the flipped classroom model in developing life skills for PAI lessons at SMK Al-Mahrusiyah Ngampel, Kediri City. This type of research is qualitative, data collected using observation, interviews, and written or oral tests. The results of the study are: (1) The flipped design of the teacher acts as a facilitator who accompanies students in doing assignments in class, in class students work on assignments based on instructions previously delivered. (2) Students watch a video that contains an explanation of the material being taught by the teacher before entering class and working on the questions or quizzes contained in the video.